Foundations of children's evangelism : How to lead a child to Christ - Gruber, Richard Allan (Dick), 1957- (Springfield, Missouri : Logion Press, 2017)
This book provides practical ideas, programs, and ways to promote kids ministry, develop outreach events, and lead a child to Christ. While the material is not all-inclusive, it is Bible-based and practical. As anyone who is involved in ministering to children knows, methods constantly evolve to meet the current cultural needs, yet the commission to reach boys and girls remains constant because God loves children.
Section 1: Research and writings -- 1. Introduction -- 2. A biblical mandate -- 3. Perspectives on evangelism of children -- 4. A practical response -- 5. Ethical considerations when giving altar calls to children -- Section 2: Practical Ideas, Programs, and Applications -- 6. The importance of prayer in evangelism -- 7. The importance of prayer when evangelizing children -- 8. Promoting your ministry -- 9. Developing evangelisitic events -- 10. Leading a child to Christ -- 11. Leading children into the Baptism in the Holy Spirit -- Appendix A: Why bring the gospel to children -- Appendix B: Hallo-What? -- Appendix C: Jesus blesses the children -- Appendix D: Five things Jesus wants you to see in Children's Ministry -- Appendix E: Leading a child to Christ -- Appendix F: Praying with children to receive the Holy Spirit.
Includes bibliographical references (197-207).
Keywords: Christian education of children